AN ANALYSIS OF FISCAL AND MONETARY POLICIES DURING THE LEADERSHIP OF UMAR IBN ABDUL AZIZ A HISTORICAL REVIEW AND ITS RELEVANCE TO CONTEMPORARY ECONOMICS - Nurpalah, Jenal; Nurdin, Irfan Bahar (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This study aims to analyze the fiscal and monetary policies implemented by Caliph Umar bin Abdul Aziz and examine the relevance of these policy principles in addressing contemporary economic challenges, particularly in terms of wealth distribution justice, price stability, and public financial management. This research employs a qualitative method using a library research approach, involving the review of classical and modern literature, including Islamic historical texts, Islamic economic literature, and relevant academic journals. The findings reveal that Umar bin Abdul Aziz applied justice- and efficiency-based fiscal policies, such as the optimization of zakat, the abolition of non-sharia levies, and equitable wealth distribution. In terms of monetary policy, he maintained currency stability and prohibited the hoarding of dinars and dirhams, which contributed to price stability and the reduction of structural poverty. In conclusion, the economic policies of Umar bin Abdul Aziz are not only historically significant but also offer a normative framework for formulating modern fiscal and monetary policies that are just, transparent, and oriented toward public welfare.